Visualizing the Periods of Stock Prices Using Non-Harmonic Analysis of the NASDAQ Composite Index Since 1985 - Matsui, Shun; Hirobayashi, Shigeki; Misawa, Tadanobu; Furukawa, Masaru (Journal of Reviews on Global Economics, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;">Abstract:<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: "Arial","sans-serif"; mso-fareast-font-family: "MS Mincho"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: EN-US;"> The prediction of stock prices is studied extensively, because of the demand from private investors and financial institutions. However, long-term prediction is difficult due to the large number of factors that affect the real market. Previous research has focused on the fluctuation patterns and fluctuation periodicity of stock prices. We have likewise focused on the periodicity of stock prices. We have used a new high-resolution frequency analysis (non-harmonic analysis) method can solve the previous problem of the frequency resolution being low. As a consequence, we have succeeded in visualizing the various periodicities of stock prices. The periodicity fluctuates gently in many periods, but we have confirmed that it fluctuated violently in periods when a sudden event occurred. We expect that this experimental result in combination with previous research will help increase predictive accuracy and will aid long-term prediction.